Groundwater and Surface Water in the Mega-Irrigation Systems of Pakistan : The Case for Conjunctive Management - van Steenbergen, Frank (World Bank, Washington, DC, 2020)
Groundwater use has increased across Pakistan, nowhere more than in the large canal-irrigated areas of the Indus basin irrigation system (IBIS). These mega-irrigation systems use surface water and groundwater, often in equal measure. The two water sources are the same source and should be managed as such. Groundwater supplied by seepage from the surface system is pumped up to complement surface water supplies. The delivery of surface water supplies determines how much groundwater is used and how much recharge will happen. In most cases, such conjunctive management will not 'cost' extra water to make significant gains in yields and support drought resilience. This case study discusses Pakistan’s contrasting experiences with conjunctive use in the Punjab and Sindh provinces and attempts to move toward conjunctive management.